THE URGENCY OF ISLAMIC BANKS FOR HAJJ FUND SERVICES - Sumarni; Giani, Malita Giani; Cici Agustina; M. Abdul Arif; Muhammad Galang Rivaldo; Doni Damara; Noprianto (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
The high level of public interest in the products and services of financial institutions, especially banks, is followed by the increasing selectiveness of the public in choosing financial institutions. This is done by the community to guarantee a protected and quality product. Only financial institutions that have a high commitment and are trusted will be chosen by the public. The success of a financial institution is marked by the number of consumers who are loyal to it. When consumers are loyal to companies or financial institutions, consumers will tend to buy and use, even make repeat purchases of the company's products or services. Consumers have a high level of loyalty which can be seen from the continuous use of a product or service. Management of Hajj fund services carried out by Islamic Banks for prospective hajj pilgrims is fully said to be optimal in providing services, it has almost been fulfilled only in terms of promoting Hajj savings products, Islamic Banks are still lacking because they have not been able to convince the public, for this reason people do not know related information regarding Hajj savings products at Islamic Banks.